Studi Komparatif Pemberian Susu Formula dan ASI Ekslusif Terhadap Kejadian ISPA Bayi Umur 0-6 Bulan - Narmawan, Narmawan; Pangestika, Yuni Widya; Tahiruddin, Tahiruddin (Journal of Holistic Nursing Science, 2020)
Acute respiratory infections (ARI) are a disease that can cause death in infants in developing countries including Indonesia. Exclusive breastfeeding and formula milk and environment are factors that influence the incidence of ARI. This study aims for determine differences in infants aged 0-6 months in Lameuru public health center. The study uses a comparative descriptive method with a retrospective study approach. Until in this study were all infants aged 0-6 months. The total sample of 116 babies. The data used are secondary data take from medical records using observation sheets. Data analysis using chi square test. The results of this study showed that babies who were given formula milk experienced more ARI namely 30,2% while babies who did not experience ARI were given 34,5% exclusive breast milk. There is a difference between formula feeding and exclusive breastfeeding for the incidence of ARI p= 0,003 (p<0,005). It was concluded that there was difference between formula feeding and exclusive breastfeeding for the incidence of ARI in infants aged 0-6 months at the Lameuru public health center. It is recommended for nursing mothers to continue breastfeeding with exclusive breast milk to their babies until the age of 6 months.